ETS-1 induces Sorafenib-resistance in hepatocellular carcinoma cells via regulating transcription factor activity of PXR. (September 2018) - Shao, Zhiyi; Li, Yibo; Dai, Wenjie; Jia, Hui; Zhang, Yingshi; Jiang, Qiyu; Chai, Yantao; Li, Xiaojuan; Sun, Huiwei; Yang, Ruichuang; Cao, Yu; Feng, Fan; et al.
Graphical abstract: Abstract: Transcription factor E26 transformation specific sequence 1 (ETS-1) is a primary regulator in the metastasis of human cancer cells, especially hepatocellular carcinoma (HCC) cells; and it would affect the prognosis of HCC patients who received chemotherapies. However, the regulatory role of ETS-1 in the resistance of HCC cells to molecular-targeting agent remains poorly understood. In the present work, we demonstrate that high ETS-1 expression correlates with poor prognosis of advanced HCC patients received Sorafenib treatment. Mechanistically, ETS-1 binds to nuclear Pregnane X receptor (PXR) directly and enhances PXR's transcription factor activity, which further leads to the induction of the PXR's downstream multi-drug resistance related genes. Overexpression of ETS-1 accelerates the metabolic clearance of Sorafenib in HCC cells and leads to the better survival and faster migration of those cells. The therapeutic studies show that ETS-1 promotes the Sorafenib-resistance of HCC tumor models and ETS-1 blockade enhances the anti-tumor capacity of Sorafenib by decreasing PXR activation. Thus, our study suggests that ETS-1 could enhance the activation of PXR and be a potential therapeutic target for overcoming Sorafenib resistance in HCC treatment.